Taxonomic position of Zhukowskia Szlach., R. Gonzalez T. & Rutk. (Cyclopogoninae, Spirantheae, Orchidaceae) - Mytnik-Ejsmont, Joanna; Rutkowski, Piotr (Biodiversity: Research and Conservation, 2006)
The Mesoamerican genus Zhukowskia Szlach. R. Gonzalez T. & Rutk. was established in 2000. An original key to species of this genus is presented. A phenetic analysis was performed (with the use of Manhattan distances for 50 characters, UPGMA and complete linkage) to verify the legitimacy of distinguishing genera within the subtribe Cyclopogoninae. The results confirmed their legitimacy and showed that Zhukowskia occupies an intermediate position between Pachygenium (Schltr.) Szlach., Tamayo & Rutk. and Sarcoglottis Presl., but is closer to the latter. Those genera differ mainly in spur structure. In Pachygenium the spur base is saccate and the line of adnation of the spur to the ovary is observable externally, while in Sarcoglottis, combined lateral sepals do not form such a line. In Zhukowskia, the form of flowers is very similar to that of Sarcoglottis, but they have a shallow, sac-like spur, which is not continuous with the ovary, and the line between the ovary and lateral sepals is visible externally.